Advancing Research on Psychosocial Stress and Aging with the Health and Retirement Study: Looking Back to Launch the Field Forward. (14th September 2018) - Crosswell, Alexandra D; Suresh, Madhuvanthi; Puterman, Eli; Gruenewald, Tara L; Lee, Jinkook; Epel, Elissa S
Abstract: Objectives: The Health and Retirement Study (HRS) was designed as an interdisciplinary study with a strong focus on health, retirement, and socioeconomic environment, to study their dynamic relationships over time in a sample of mid-life adults. The study includes validated self-report measures and individual items that capture the experiences of stressful events (stressor exposures) and subjective assessments of stress (perceived stress) within specific life domains. Methods: This article reviews and catalogs the peer-reviewed publications that have used the HRS to examine associations between psychosocial stress measures and psychological, physical health, and economic outcomes. Results: We describe the research to date using HRS measures of the following stress types: traumatic and life events, childhood adversity, caregiving and other chronic stressors, discrimination, social strain and loneliness, work stress, and neighborhood disorder. We highlight how to take further advantage of the longitudinal study to test complex biopsychosocial models of healthy aging. Discussion: The HRS provides one of the most comprehensive assessments of psychosocial stress in existing population-based studies and offers the potential for a deeper understanding of how psychosocial factors are related to healthy aging trajectories. The next generation of research examining stress and trajectories of aging in the HRS should test complex longitudinal and mediational relationships, include contextual factors in analyses, and include more collaboration between psychologists and population health researchers.